Determinants of Multidimensional Human Development and Developing to Developed Countries in UNDP Classification - Elina, Riskiana (Jurnal Dinamika Ekonomi Pembangunan, 2025)
This study analyzes the factors that affect the Inequality-Adjusted Human Development Index (IHDI) in developing countries based on the UNDP classification. IHDI is used because it describes the quality of human development after considering inequality in the dimensions of education, health, and income. The study uses 2008–2023 panel data obtained from UNDP, the World Bank, the ITU, and other international sources. The independent variables analyzed include Adjusted Net Savings (ANS), Current Health Expenditure (CH), Income Share Held by the Bottom 40 Percent (INS), Life Expectancy (LE), Years of Schooling (YS), Gross National Income per capita (GNI), Gender Inequality Index (GII), and Mean Years of Schooling (MYS). Model selection was conducted using the Chow Test and Hausman Test, which established the Fixed Effect Model as the best specification. The results show that CH, LE, YS, GNI, and MYS have a positive and significant effect on IHDI, emphasizing the importance of improving education, health, and income in strengthening the quality of human development. INS has a negative and significant effect, indicating that increasing the income share of the bottom 40 percent has not improved the equity of human development outcomes without corresponding improvements in basic services. Meanwhile, ANS and GII do not have a significant influence. These findings emphasize that inclusive human development requires strengthening capabilities through education, health, and equitable income growth.